PKA-mediated phosphorylation of EPEC-Tir at serine residues 434 and 463: A novel pathway in regulating Rac1 GTPase function - Backert, Steffen; Kenny, Brendan; Gerhard, Ralf; Tegtmeyer, Nicole; Brandt, Sabine (Gut Microbes, 2010)
Type-III or type-IV secretion systems of many Gram-negative bacterial pathogens inject effector proteins into host cells that modulate cellular functions in their favour. A preferred target of these effectors is the actin-cytoskeleton as shown by studies using the gastric pathogens Helicobacter pylori (H. pylori) and enteropathogenic Escherichia coli (EPEC). We recently developed a co-infection approach to study effector protein function and molecular mechanisms by which they highjack cellular signalling cascades. This is exemplified by our observation that EPEC profoundly blocks H. pylori-induced epithelial cell scattering and elongation, a disease-related event requiring the activity of small Rho GTPase Rac1. While this suppressive effect is dependent on the effector protein Tir and the outer-membrane protein Intimin, it unexpectedly revealed evidence for Tir-signalling independent of phosphorylation of Tir at tyrosine residues 454 and 474. Instead, our studies revealed a previously unidentified function for protein kinase A (PKA)- mediated phosphorylation of Tir at serine residues 434 and 463. We demonstrated that EPEC infection activates PKA for Tir phosphorylation. Activated PKA then phosphorylates Rac1 at its serine residue 71 associated with reduced GTP-load and inhibited cell elongation. Phosphorylation of Rho GTPases such as Rac1 might be an interesting novel strategy in microbial pathogenesis. © 2010 Landes Bioscience.
Created from Fastlane, Scopus look-up
Keywords: Molecular pathogenesis; Pathogenicity island; type III and type IV secretion; Virulence